Fragility of the provision of local public goods to private and collective risks - Cárdenas, J.C.; Janssen, Marco A.; Ale, M.; Bastakoti, Ram C.; Bernal, A.; Chalermphol, J.; Gong, Y.; Shin, H.; Shivakoti, G.P.; Wang, Y.; Anderies, J.M. (National Academy of Sciences, 2017)
Smallholder agricultural systems, strongly dependent on water resources and investments in shared infrastructure, make a significant contribution to food security in developing countries. These communities are being increasingly integrated into the global economy and are exposed to new global climate-related risks that may affect their willingness to cooperate in community-level collective action problems. We performed field experiments on public goods with private and collective risks in 118 small-scale rice-producing communities in four countries. Our results indicate that increasing the integration of those communities with the broader economic system is associated with lower investments in public goods when facing collective risks. These findings indicate that local public good provision may be negatively affected by collective risks, especially in communities more integrated with the market economy.